Osteoporosis in men - Misiorowski, Waldemar (Menopause Review/Przegląd Menopauzalny, 2017)
Osteoporotic fractures are the leading cause of morbidity and mortality among aging men. 30% of all hip fractures occur in men, and mortality resulting from not only the hip fracture, but also the spine and other major osteoporotic fractures, is significantly higher in men than in women. As in women, hypogonadism is the best documented risk factor for developing osteoporosis in men. In older men, testosterone levels are negatively correlated with the risk of fractures, and it seems that this age-related testosterone deficiency should not be considered as one of the many causes of secondary osteoporosis, rather one of the major and most important mechanisms of senile osteoporosis. Acute hypogonadism induced by ablation treatment for prostate cancer (surgical or pharmacological castration, antiandrogen therapy) is associated with an extremely high risk of fracture. Other documented causes of bone loss in men are cigarette smoking and alcohol abuse, and a number of diseases that require corticosteroid treatment. Pharmacotherapy of osteoporosis should be recommended to all men with a diagnosed osteoporotic fracture and all men with a high 10-year absolute fracture risk (FRAXTM). Not all drugs registered for the treatment of postmenopausal osteoporosis have been registered for the treatment of osteoporosis in men, and others have not been the subject of long-term and costly clinical trials required for such registration. The risk reduction of new fractures was documented only for treatment with zoledronic acid. Risedronate, strontium ranelate, teriparatide, and denosumab in men increase in bone mineral density comparable to that seen in postmenopausal women.